Pengaruh Kualitas Pelayanan dan Peran Pendamping terhadap Kepuasan Masyarakat Penerima Manfaat Bantuan Program Kelurga Harapan (PKH) - Wiwi Adilah; Hendri Sucipto; Indah Dewi Mulyani (Jurnal Manajemen Riset Inovasi, 2023)
The purpose of this study was to determine the partial and simultaneous effect of service quality and the role of chaperones on satisfaction with the delivery of PKH assistance in Sidamulya village. For research sampling, researchers used the Slovin technique, so the sample used was 76 people. Data collection techniques using questionnaires and documentation. Test the validity of the instrument using Product Moment correlation and reliability testing using Cronbach's Alpha. The classic assumption test consists of the normality test, multicollinearity test and heteroscedasticity test. The hypothesis test consists of a partial test (t test), simultaneous test (F test) and multiple linear regression tests.The service quality variable (X1) has a significant and positive effect on community satisfaction (Y). This is indicated by the significant value of 0.000 <0.05 and the t-count value of 2,224 > the t-table value of 1,665. The Chaperone's Role variable has a positive and significant effect on the satisfaction of beneficiaries of PKH assistance. the results of the analysis are proven by a significant value of 0.003 <0.05 and a t-count value of 5,077 > a t-table value of 1,665. Variables Influence of Public Service Quality and Companion Role have a positive and significant effect on the satisfaction of beneficiaries of PKH assistance. 15.810 while the F table value is 3.97, it can be seen that the calculated F value > F table, with a significant level of 0.000 <0.05.